A Delphi Consensus Approach to Challenging Case Scenarios in Moderate-to-Severe Psoriasis: Part 1 - Strober, Bruce E. (Springer Healthcare Communications, 2012)
INTRODUCTION: Traditional clinical trials in psoriasis exclude a significant proportion of patients with complex disease and comorbidities. A consensus panel of 14 experts in the field of psoriasis was formed to conduct a Delphi method exercise to identify difficult-to-treat psoriasis clinical scenarios and to rank treatment approaches. METHODS: The exercise consisted of both survey questionnaires and a live meeting to review and discuss current data (as of 2009, when the exercise was conducted) and arrive at a consensus for optimal treatment options. Seventy difficult treatment scenarios were identified, and the top 24 were selected for discussion at the live meeting. RESULTS: Six of the 24 discussed case scenarios are presented in this article (another five are presented in Part 2): (1) psoriasis with human papilloma virus-induced cervical or anogenital dysplasia; (2) concomitant psoriasis and systemic lupus erythematosus; (3) severe psoriatic nail disease causing functional or emotional impairment; (4) psoriasis therapies that potentially reduce cardiovascular morbidity and mortality; (5) older patients (≥65 years of age) with psoriasis; and (6) severe scalp psoriasis that is unresponsive to topical therapy. CONCLUSION: The Delphi exercise resulted in guidelines for practicing physicians to utilize when confronted with challenging patients with psoriasis.